(untitled) (The Pakistan Development Review, 2014)
The paper assesses the energy sector’s foreign exchange requirements for meeting energy consumption and for capital expenditures, and identifies its implications for the country’s macroeconomic policy and management. We develop a conceptual model for projecting the energy sector’s long-term requirements for foreign exchange. The model indicates that the country’s chronic dependence on oil imports is likely to expose the economy to high and volatile oil prices. A fundamental issue for Pakistan is how the energy projects requiring large inflows of foreign capital and technology will be financed. The main implication of our analysis is that there will be continuing pressure on the country’s foreign exchange resources. The demand for foreign exchange by the year 2024-25 is projected to be US 20-21 billion without the FDI in new power generation. However, when we include the requirements of foreign exchange for capital expenditure, the total FX requirements are in the range of US 23- 24 billion. An implication of the country’s chronic energy deficiency is that the macroeconomic policies, particularly the foreign exchange rate policy, need to be redefined to reflect the projected demands on hard currencies and their expected scarcity value. It is likely that Pakistan will remain dependent on foreign imports to meet its energy requirements for a long time and will need to generate commensurate foreign exchange resources to ensure longterm energy security. JEL classification: E66, F37, Q43 Keywords: Macroeconomic Policy, Exchange Rate Policy, Energy Security